Economic growth and liberalization: A time series analysis for Mexico - Hernández Trillo, Fausto (Estudios Económicos de El Colegio de México, 1993)
This paper presents a methodology to measure the effects of economic liberalization and deregulation on the Mexican economic growth in the long run. The methodology can determine whether there has been a permanent change in the rate of growth. The results show that the increase in the Mexican case has been transitory and that there has been a change in the level of growth rather than in the rate. This suggests that technology and labor productivity have not changed substantially, and hence that the growth is explained by the use of idle capacity. However, since it takes time for technological changes to appear, these results have to be taken as preliminary.